SIMULATION OF SULFUR DIOXIDE REMOVAL FROM A GAS STREAM IN A FLUIDIZED-BED REACTOR (Journal of Engineering, 2010)
The object of this work is to model and simulate a fluidized bed desulfurization reactor by coupling a reactor kinetic model with a fluidized bed model based on two –phase theory(bubbling-bed model) proposed by Kunni and Levenspiel(1968).This model is useful for analysis of a reaction involving gas and solid. It generates the conversion data with respect to reaction time of both reacting gas and solids in a continuous flow(for both gas and solids) in fluidized bed. The flue gas or stack gas from a combustor which normally contains sulfur dioxide mixed with excess air is used as the fluidizing gas with calcium oxide as the fluidized solids . Calcium oxide is quite capable of reacting with 2 SO to effect its removal from the gas phase according to the exothermic reaction :s  CaO + g  SO2 + 2 1g  O2 s  CaSO4 + HeatThe effects of the solid feed rate, SO2 concentration in the flue gas, bed height, bed diameter, particle size, fluidizing velocity and operating temperature on the extent of conversion of both gas and solid were investigated, for a fixed feed rate of flue gas and SO2concentration (50.000 cm3/sec ,3-5% by volume)at temperature range of (950-1000oC)and pressure 1 atm.